2010
DOI: 10.1111/j.1365-2818.2009.03358.x
|View full text |Cite
|
Sign up to set email alerts
|

Spine micromorphology of normal and hyperhydric Mammillaria gracilis Pfeiff. (Cactaceae) shoots

Abstract: Artificial conditions of tissue culture affect growth and physiology of crassulacean acid metabolism plants which often results in formation of hyperhydric shoots. In in vitro conditions Mammillaria gracilis Pfeiff. (Cactaceae) growth switches from organized to unorganized way, producing a habituated organogenic callus which simultaneously regenerates morphologically normal as well as altered hyperhydric shoots. In this study, influence of tissue culture conditions on morphology of cactus spines of normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This is another case that can be attributed to watering under home cultivation. The only apparently discordant data are those from Peharec et al (2010), where the "hyperhydric" stems of Mammillaria gracilis Pfeiff. presented shorter spines when compared to pot grown plants.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is another case that can be attributed to watering under home cultivation. The only apparently discordant data are those from Peharec et al (2010), where the "hyperhydric" stems of Mammillaria gracilis Pfeiff. presented shorter spines when compared to pot grown plants.…”
Section: Discussionmentioning
confidence: 88%
“…All rights reserved. Schmalzel et al, 2004;Peharec et al, 2010) and ecological interactions (Pérez-Harguindeguy et al, 2013). Nobel (1983), Loik (2008), and Drezner (2011) found that the spine coverage directly affects the downward solar radiation on the stem.…”
Section: Introductionmentioning
confidence: 97%
“…For ornamental cacti, as are the species described here, the presence of spines is a positive element for their decorative traits. Peharec et al (2010) evaluated the spines of pot-grown Mammillaria plants and in vitro-regenerated shoots and found that the pot-grown plants had 16-17 spines per areole, whereas the in vitro-grown shoots were normal but displayed a lower number of spines (11-12). Parra et al (2010) argued that genetic diversity should be conserved and should be promoted by artificial selection, which, despite the high levels of gene flow, moderate the genetic structure between wild and managed populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large variation of spine traits within single species has been described ( Peharec et al 2010 ), there is no extant report describing spine variation within an areole. Since the spines grow from the same lateral bud, low variation of anatomical and morphological parameters would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is evidence that spine development is influenced by genetic ( Mihalte and Sestras 2012 ) and environmental conditions as water availability or solar radiation can modified spine growth (e.g. Peharec et al 2010 , Menezes et al 2015 ). Nevertheless, to the best of our knowledge, there is no prior study analyzing spine and fiber structure variation within areoles, individuals or populations, with the exception of variation in spine number and length (e.g.…”
Section: Introductionmentioning
confidence: 99%